The Remix Manual - Langford, Simon (Routledge, 2014)
Can you turn a soulful ballad into a hit dance track, or make any Billboard hit your own? With this all-in-one guide to remixing, you can! Whether you're just beginning to mix tracks or you're already a professional DJ or producer, this step-by-step guide takes you through the entire process of making your own professional-quality remixes. Author Simon Langford, a renowned remixer/producer with over 300 remixes and chart-toppers under his belt, shares his years of experience and expertise in the most in-depth guide to remixing on the market. The Remix Manual covers creative processes, technical, legal, and contractual issues, and includes a unique remix "walk-through," and useful contacts and links. The companion website, www.TheRemixManual.com, provides source files that illustrate all stages of the remix, as well as additional interviews and walk-throughs, a Buyer's Guide, video tutorials, and demo versions of the hottest mixing software